2016
DOI: 10.1093/jmcb/mjw029
|View full text |Cite
|
Sign up to set email alerts
|

BDNF rescues prefrontal dysfunction elicited by pyramidal neuron-specific DTNBP1 deletion in vivo

Abstract: Dystrobrevin-binding protein 1 (Dtnbp1) is one of the earliest identified schizophrenia susceptibility genes. Reduced expression of DTNBP1 is commonly found in brain areas of schizophrenic patients. Dtnbp1-null mutant mice exhibit abnormalities in behaviors and impairments in neuronal activities. However, how diminished DTNBP1 expression contributes to clinical relevant features of schizophrenia remains to be illustrated. Here, using a conditional Dtnbp1 knockout mouse line, we identified an in vivo schizophre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 80 publications
1
25
0
Order By: Relevance
“…This inconsistency between increased spine density without alterations of excitatory neurotransmission in Dys −/− mice, could be due to the increased proportion of thin, highly unstable spines, which do not normally make functional synapses 70 . However, we found that that the frequency of GABA A -receptor-mediated spontaneous IPSCs, but not their amplitude, was elevated in Dys −/− mice, which is consistent with the role dysbindin-1 plays in regulating GABA release 9,20 . The inhibition/excitation ratio was enhanced in neurons of Dys −/− mice, indicating that the activity of excitatory neurons could be inhibited in these animals.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This inconsistency between increased spine density without alterations of excitatory neurotransmission in Dys −/− mice, could be due to the increased proportion of thin, highly unstable spines, which do not normally make functional synapses 70 . However, we found that that the frequency of GABA A -receptor-mediated spontaneous IPSCs, but not their amplitude, was elevated in Dys −/− mice, which is consistent with the role dysbindin-1 plays in regulating GABA release 9,20 . The inhibition/excitation ratio was enhanced in neurons of Dys −/− mice, indicating that the activity of excitatory neurons could be inhibited in these animals.…”
Section: Discussionsupporting
confidence: 82%
“…The observed differences reinforce the view that the mutation effects may be brain region specific and be translated into region-specific functional modifications (e.g., distinct synaptic and neuronal changes). In the mPFC, impaired GABAergic transmission and fewer inhibitory synapses on pyramidal neurons of Dys −/− mice was apparently due to reduced activity-dependent secretion of brain-derived neurotrophic factor (BDNF) from pyramidal neurons 9,20 . Thus, in the BLA of Dys −/− mice, it is possible that BDNF release is increased from excitatory neurons, thereby enhancing BLA GABAergic transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that GFP protein driven by CamKII promoter in AAV1 virus is mostly expressed in excitatory neurons (i.e., only 1% GFP positive neurons were GABAergic neurons) once being injected into mouse prelimbic cortex (Zhang et al, 2017). In this study, for calcium imaging experiments, we unilaterally injected AAV1.CamKII.GCaMP6f.WPRE.SV40 virus (University of Pennsylvania Vector Core, 500 nl with a titer of 2.76e13 GC/ml) into the dorsal region of the mouse prelimbic cortex, using the stereotactic coordinates (A/P: +1.9 mm, M/L: +0.3 mm, D/V: −1.7 mm).…”
Section: Star Methodsmentioning
confidence: 99%
“…BDNF regulates neuronal proliferation, survival, and brain development, and represents a potentially relevant gene for schizophrenia [ 20 ]. Reduced expression of cerebral BDNF has been implicated in the pathophysiology of schizophrenia and has been considered to be related to the deficit of PPI, a behavioral endophenotype of schizophrenia [ 7 , 21 ]. There was an altered PPI of the acoustic startle response in an early postnatal hypoxia BDNF-deficient mouse model of schizophrenia [ 22 ].…”
Section: Discussionmentioning
confidence: 99%